eCM 2013
DOI: 10.22203/ecm.v025a09
|View full text |Cite
|
Sign up to set email alerts
|

Biologic scaffolds for musculotendinous tissue repair

Abstract: Traumatic injuries to the musculoskeletal system are common events and volumetric muscle loss (VML) is no longer a rare occurrence. Surgical intervention is typically the only option for restoration of partial function. Surgical intervention for VML however does not regenerate the lost tissue and typically results in alterations of both the anatomy and biomechanics at the site of injury. Non-traditional approaches to the restoration of functional musculoskeletal tissue, including those provided by tissue engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 156 publications
0
51
0
Order By: Relevance
“…In addition, the use of allografts is further limited by their higher overall surgical costs; approximately US$ 1,000 extra per clinical case [305,306]. For these reasons, the use of xenografts took off, with numerous products currently available [307,308]. Although positive functional scores and improved movement as early as 6 months post-operation have been reported [309], many studies have demonstrated high failure rates and tearing incidents [310][311][312][313], which may be attributed to processing conditions (e.g.…”
Section: Tissue Grafts -The Top-down Approach For Tendon Repairmentioning
confidence: 99%
“…In addition, the use of allografts is further limited by their higher overall surgical costs; approximately US$ 1,000 extra per clinical case [305,306]. For these reasons, the use of xenografts took off, with numerous products currently available [307,308]. Although positive functional scores and improved movement as early as 6 months post-operation have been reported [309], many studies have demonstrated high failure rates and tearing incidents [310][311][312][313], which may be attributed to processing conditions (e.g.…”
Section: Tissue Grafts -The Top-down Approach For Tendon Repairmentioning
confidence: 99%
“…23 Because biological meshes have the advantage of being biocompatible and tissue inductive, more and more surgeons and researchers have become interested in the biological meshes for pelvic floor reconstruction. 24,25 However, recurrence rates as high as 39% have been reported for biological mesh derived from fascia lata because of mechanical strength issues and rate of biodegradation. 26 We have developed biodegradable meshes containing PLCL and Fg via electrospinning technology.…”
Section: Discussionmentioning
confidence: 99%
“…Decellularized dermal graft is one of the most widely used products in a variety of reconstructive practices such as Histologic evaluations by H&E and IHC, a, e H&E staining of normal sphincter, b, f desmin staining of normal sphincter, c, g H&E staining of the sphincter after BPNT, d, h desmin staining of the sphincter after BPNT; in both H&E and IHC staining, striated muscular layer around the denervated urethral external sphincter is thin and atrophied, and the collagenous connective tissue between fibers is increased. (Magnification: a-d ×10 and e-h ×40) wound repair [22], cleft palate repair [23], tendon repair [24], breast prosthesis [25], muscle repair [26] and other soft tissues [21]. These grafts have been shown to be effective scaffolds in attracting host cell migration and proliferation in vivo and also to perform as a resistant material in high tension sites [27].…”
Section: Discussionmentioning
confidence: 99%